Co-infection of Haemonchus contortus and Trichostrongylus spp. among livestock in Malaysia as revealed by amplification and sequencing of the internal transcribed spacer II DNA region - Thong, T.K.; Panchadcharam, C.; Low, V.L.; Lee, S.C.; Ngui, R.; Sharma, R.S.K.; Lim, Y.A.L. (BioMed Central, 2014)
Background